Molecular landscape of lung cancer: insights into therapeutic targets and clinical outcomes - Saloni Mangal; Abhijit Debnath; Rupa Mazumder; Avijit Mazumder; Rajesh Kumar Singh; Jahanvi Sanchitra; S.K. Asif Jan; Pratibha Pandey; Bimlesh Kumar; Anil Kumar Singh (All Life)
Lung cancer is the leading cause of cancer-related deaths globally, accounting for 1.8 million fatalities in 2020. Genetic mutations, chromosomal abnormalities, transcription factors, mutations in tumor suppressor genes, and mutations in oncogenes have all been associated with an increased risk of LC development. Heterogeneity of the disease, resistance to chemotherapy, and side effects such as nausea and vomiting, fatigue, anemia, neuropathy, hair loss, and skin and nail changes are associated with conventional therapeutics such as chemotherapy, radiation therapy, and targeted therapy. Thus, the treatment of the disease urgently requires the discovery of novel therapeutic approaches. This review identifies and discusses key molecular and genetic targets for LC therapy, highlighting recent advancements and potential clinical applications. Our efforts encompass all biological targets and aim to increase our understanding of these processes to better comprehend the disease's molecular mechanisms and develop new drugs and more effective LC treatments.